The Besemah Community’s Indigenous Knowledge of Tebat Bukit Conservation in Tebat Benawa Village - Efendi, Doki; Meilinda, Meilinda; Riyanto, Riyanto (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This research aims at finding out the form of indigenous knowledge of the Tebat Benawa Community toward Tebat Bukit conservation. The researchers conducted this descriptive study from December 2019 to January 2020. The object of the study was the Tebat Benawa Village Community. The data were collected through literature study, observation, and semi-structured interviews. The results show that the community has five indigenous knowledge in the implementation of Tebat Bukit conservation which is classified into three indicators: the availability of tebat (artificial lake) water, Tebat Bukit, and ghumbus; the use of tebat water called Siring Ayik; tebat and its water management, namely nebasi jalan, ghumbus, and society knowledge transfer in preserving Tebat Bukit through direct experience sharing. The experience sharing is conducted by fishing in tebat, implementing indigenous tradition, socializing with the village administration, giving parental advice, and fostering petatah-petitih (oral tradition on local wisdom).